Runner - Perry, Thomas, 1947- (Perry, Thomas, 1947- Jane Whitefield novel., 2009)
In the sixth book of the Jane Whitefield series, Jane finds herself giving up her promise of retirement when, in the aftermath of a bomb explosion, she comes to the assistance of a young pregnant girl, who is being tracked down by a team of hired hunters.